A Dialogical Exploration of Student Teacher Reflections: From Notions of Insideness and Outsideness to Pedagogical Alongsideness - Josephine Moate (MDPI AG, 2023)
This article offers a dialogical exploration of student teachers' reflections on notions of insideness and outsideness, the focal themes of an Erasmus+ ten-day intensive programme (IP). The arts-based, interdisciplinary IP involved 32 student participants and twelve members of staff from eight European universities hosted by the University of Jyväskylä, Finland. The data for this paper are based on the final written essays of student participants as they reflected on their understanding of outsideness and insideness at the end of the IP. The dialogic approach used in the analysis allows for a careful exploration of how the students attended to different experiences, surmised the meaning of insideness and outsideness, and used these reflections to develop their pedagogical response. The findings highlight how the participants drew on their own experiences and relationships within and beyond the IP to navigate and negotiate their pedagogical understanding. This study offers useful insights into the formation of pedagogical understanding as well as the role and responsibilities of teacher education in guiding this formative process, all the more important in times of emergencies.